PENGARUH MODAL KERJA DAN JUMLAH SAHAM YANG BEREDAR TERHADAP LIKUIDITAS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Marpaung, Santa Gasari; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to examine partially and simultaneously the effect of working capital and the number of outstanding shares on liquidity. Where the independent variables in this study are working capital and the number of shares outstanding while the dependent variable is liquidity. The sample used is secondary data derived from the financial statements of textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2011 to 2015This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and determination coefficient test. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate that the variables of working capital and the number of shares that are circulated in a persial (t test) have no effect on liquidity in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Simultaneous test results (f) show the influence of working capital variables and the number of shares outstanding on liquidity in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock ExchangeKeywords: Working Capital, Number of Circulated Shares, and Liquidity